ACTB: ZMIZ2-rearranged adnexal carcinoma: a second case - Dehner, Carina; Pissaloux, Daniel; Thamphya, Brice; Tirode, Franck; Deimling, Andreas von; Guo, Ruifeng R.; Wieland, Carilyn; de la Fouchardière, Arnaud; Kervarrec, Thibault (Virchows Archiv, 2025)
A case of cutaneous adnexal neoplasm with unusual squamoid morphology and harboring an in frame ACTB::ZMIZ2 fusion transcript was recently described. Herein, we report a second case of adnexal carcinoma harboring similar morphology and an identical in frame ACTB::ZMIZ2 fusion transcript. This 2.2-cm mass was removed from the axilla of a 17-year-old woman. Microscopic examination revealed a large nodular and infiltrative tumor invading the dermis composed of sheets and nests frequently centered by large areas of keratinization. Molecular investigation revealed an in frame ACTB::ZMIZ2 fusion transcript. Clustering analysis revealed close proximity of this case with the ACTB::ZMIZ2-fused adnexal tumor previously reported. Herein, we report a second case of adnexal tumor with ACTB::ZMIZ2 fusion arising in a young adult suggesting that ACTB::ZMIZ2 fusion might be a defining genetic event, specific of a rare and previously undescribed adnexal tumor entity.
Gesehen am 28.07.2025